Pre-service teachers' goals and future-time extension, concerns, and well-being - Hagger, H; Malmberg, L (2011)
Human goal-processes are conceptualised in an action-theoretic model of motivation, in line with discourse on self-directed teachers. Eighty-eight pre-service teachers reported ideographic professionally-related goals and concerns, future-time extension of the goals, and well-being (self-esteem and depression). Thirteen goal and fifteen concern categories were identified. When the goals were ordered in a perceived future time-sequence these did not reflect discrete developmental stages of teachers. Goals were related to concerns in six content domains demonstrating the utility of investigating both. Goals and concerns were to some extent related to well-being. © 2010 Elsevier Ltd.